The Effect of Audiovisual Learning System on Self-Efficacy and Critical Thinking Ability in Science Lessons on Human Digestive System Materials Science - Yasin Yasin; Abin Syamsudin; Daeng Arifin; Waska Warta (Syntax Corporation Indonesia, 2021)
tudents' critical thinking ability in teaching and learning activities on human digestive system material is still low, where students are less skilled in collecting and analyzing data, relevant facts and identifying problems, so students have difficulty in solving problems with alternatives that fit the logic. Based on the results of the hypothetical test analysis obtained t hit > t daf (1.67), then accept. Hi means that there is an influence on the use of audiovisual learning media on critical thinking ability in human digestive system materials in grade VIII students of SMP Negeri 1 And SMP Negeri 2 Sindang Indramayu Regency. From the calculation of t test above obtained t count = 4,957 while t table at the level of trust 95% (significance 5%) with dk numerator is 1.70. Because t count (4,957) > t table (1,70) Hi accepted means there is an influence on the use of audiovisual learning media on self-efficacy in human digestive system materials in grade VIII students smp negeri 1 Filled And SMP Negeri 2 Sindang Indramayu. The result of this study is a description of the efficacy of students of grade VIII SMP Negeri 1 Filled And SMP Negeri 2 Sindang Indramayu Regency, by using audiovisual media learning system in human digestive system materials belongs to high category. There is an influence of audiovisual media learning system on self-efficacy on human digestive system materials in students VIII SMP Negeri 1 Filled And SMP Negeri 2 Sindang Indramayu.